Home health nurse decision-making regarding visit intensity planning for newly admitted patients: a qualitative descriptive study. Issue 3 (3rd July 2018) - Irani, Elliane; Hirschman, Karen B.; Cacchione, Pamela Z.; Bowles, Kathryn H.
ABSTRACT: Despite patients referred to home health having diverse and complex needs, it is unknown how nurses develop personalized visit plans. In this qualitative descriptive study, we interviewed 26 nurses from three agencies about their decision-making process to determine visit intensity and analyzed data using directed content analysis. Following a multifactorial assessment of the patient, nurses relied on their experience and their agency's protocols to develop the personalized visit plan. They revised the plan based on changes in the patient's clinical condition, engagement, and caregiver availability. Findings suggest strategies to improve visit planning and positively influence outcomes of home health patients.